DIGITALIZATION OF LOGISTICS ENTERPRISES' ACTIVITIES - Laura Davirova Abduvaliyevna (Web of Journals Publishing, 2025)
This article examines the challenges and opportunities for developing digital logistics in Uzbekistan. The primary objective of the study is to identify ways to enhance efficiency and achieve economic benefits through the digitalization of logistics processes. The study explores the impact of digital technologies, including the advantages of IoT and electronic management systems. Based on statistical analysis, international practices, and local case studies, scientific-methodological and practical recommendations are proposed.
Keywords: Digital economy, logistics, digital technologies, globalization, digital transformation, efficiency, digital logistics, strategy, competition, transport system, digital platform, concept.